Muscarinic and nicotinic receptors raise intracellular Ca2+ levels in rat carotid body type I cells. - Dasso, L; Buckler, K; Vaughan-Jones, R (1997)
1. The effects of cholinergic agonists upon intracellular free Ca2+ levels ([Ca2+]i) have been studied in enzymically isolated rat carotid body single type I cells, using indo-1. 2. Acetylcholine (ACh) dose-dependently increased [Ca2+]i in 55% of cells studied (EC50 = 13 microM). These [Ca2+]i rises were partially inhibited by atropine or mecamylamine. 3. Specific nicotinic and muscarinic agonists also elevated [Ca2+]i in a dose-dependent manner (nicotine, EC50 = 15 microM; methacholine, EC50 = 20 microM). 4. While the majority of the ACh-sensitive cells responded to both classes of cholinergic agonist, 29% responded exclusively to nicotinic stimulation and 9% responded exclusively to muscarinic stimulation. 5. In the presence of nicotinic agonists, Ca2+i responses were transient. In the presence of muscarinic agonists, Ca2+i responses consisted of an initial rise, which then declined to a lower plateau level. 6. Nicotinic responses were rapidly abolished in Ca(2+)-free medium, suggesting that they are dependent on Ca2+ influx. 7. The plateau component of the muscarinic-activated response was also abolished in Ca(2+)-free conditions. The rapid initial [Ca2+]i rise, however, could still be evoked after several minutes in Ca(2+)-free medium. Muscarine also increased Mn2+ quenching of intracellular fura-2 fluorescence. These data suggest that the full muscarinic response depends on both Ca2+ release from intracellular stores and Ca2+o influx. 8. The results indicate that, in rat carotid body type I cells, both nicotinic and muscarinic acetylcholine receptors increase [Ca2+]i, but achieve this via different mechanisms. ACh may therefore play a role in carotid body function by modulating Ca2+i in the chemosensory type I cells.